Philanthropy Kepada Non Muslim Dan Pengaruhnya Terhadap Pluralisme Kaum Muslim (Perspektif Maqashid Syariah) - M Soleh Mauludin; Zakiyatus Soimah (El-Faqih : Jurnal Pemikiran dan Hukum Islam, 2022)
This research aims to see the extent of maqashid sharia's view of philanthropy practices in the form of the construction of livable houses carried out by Jamaah Thoriqoh Shiddiqiyah towards underprivileged non-Muslim communities, as well as its influence on the pluralism of the surrounding Muslim community. With a qualitative approach, and using the theory of pluralism and philanthropy, this study resulted in the conclusion that the Muslim community around the construction site of livable houses participated in this movement and experienced a change in attitude. If originally they tended to limit themselves from all activities and traditions involving non-Muslims, then now they are experiencing a change to be more active and willing to blend in with people with different backgrounds. In the view of Maqashid Sharia, this reality is able to maintain the continuity of soul, property, and religion